O conhecimento acadêmico-científico em educação musical na revista da ABEM: um discurso histórico-narrativo - Almeida, Bruno Felix da Costa (2024)
The constitution of this Doctoral Thesis in Education is delimited considering the academic-scientific communication in Music Education published in the editions of the Revista da Associação Brasileira de Educação Musical – Revista da ABEM. To this end, it was led by the question: What is the impact of knowledge in Music Education, developed by Brazilian researchers, on the production of knowledge conveyed in the editions of the Revista da ABEM, published between 1992 and 2023? As a general objective, it sought to understand the impact of knowledge in Music Education, produced by Brazilian authors, from the editions of the Revista da ABEM, published between 1992 and 2023. The importance of the study emerged in the understanding that all scientific communication implies movements of choices, debates, political actions and prospection of theoretical-academic-scientific development. For its development, the methodology used was constituted with an emphasis on the Theory for Historical-Narrative Knowledge, elaborated during the constitution of the research and with an emphasis on the studies of Morin (2020; 2019; 2017). Thus, the historicized narratives – archives, documents and recorded memories – became effective as subsidies to the knowledge and to know oneself historically, in the interlocution between them and the researcher's act of interrogating them, knowledge about certain educational-musical facts that occurred, revisiting the past time in search of (re)significations and perceptions about the lived world. The Theoretical-Reflective Framework was proposed based on Ricoeur's considerations about time and historical narrative (2010a, 2010b, 2010c). However, knowing the actions and, mainly, getting closer to the ways of sharing knowledge in Music Education used by ABEM allowed for deepening about its periodical Revista da ABEM. The Textual Analysis of the contents related in its editions allowed us to think about possibilities to understand the importance of the impact of the production and sharing of knowledge in Music Education, to the construction of knowledge destined to the field of study. This research proposes as a Thesis the Cycle of Sharing of Academic-Scientific Knowledge in Music Education, which presupposes, from the production to the sharing of knowledge in Music Education, procedural steps for its development. It is, therefore, such approximations to historicized and shared narratives that enable the (re)configuration of knowledge in Music Education that constitute this Doctoral Thesis in Education.